Foreign language anxiety and achievement: systematic review - Al-Shboul, Murad M.; Sheikh Ahmad, Ismail; Nordin, Mohamad Sahari; Abdul Rahman, Zainurin (Canadian Center of Science and Education, 2013)
This systematic review of literature on foreign language anxiety and its relationship with achievement is additional clarification to the earlier works and reviews concerned with this issue. Firstly, it defines the foreign language anxiety concept where eventually foreign language anxiety is differentiated from other related concepts. Secondly, it reviews the existing studies where the constructs of foreign languages are determined. Finally, it presents the studies that concern foreign language anxiety and achievement in a systematic way where different settings, languages, learners’ stages and disciplines were involved. Keywords: foreign language anxiety, foreign language anxiety and achievement, systematic review